VOGELL’S APROXIMATION METHOD DALAM OPTIMALISASI BIAYA TRANSPORTASI PENGIRIMAN KORAN PADA PT. ARAH MEDIALOG PEMBANGUNAN - Nico Hermanto; Eni Heni Hermaliani; Entin Sutinah (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
The accuracy of delivered newspaper to customers affects the quality of service. Besides, the cost of shipping is not stable result of defeat in competitive because it can not offer the lowest prices of the products to the customers and also affect the company's revenue. Required modeling is right for newspaper delivery problems in PT. Arah Medialog Pembangunan is to transport models and techniques completion of transport, so that costs transport can be optimized delivery of newspapers. Solving method is the method of Vogel's Approximation Method (VAM). The results show that the total cost of newspaper delivery to West Java optimal for Rp.1.603.270, smaller than a newspaper delivery started transportation costs incurred by the company using its own way. Mechanical completion of transportation using Vogel's Approximation Method (VAM) is applied to the application POM-QM For Windows 3.Keyword—Newspaper delivery, optimization, transportation fees, Vogel's Approximation Method (VAM).